Two transmembrane transcriptional regulators coordinate to activate chitin-induced natural transformation in Vibrio cholerae. - Allison C Hullinger; Virginia E Green; Catherine A Klancher; Triana N Dalia; Ankur B Dalia (PLoS Genetics)
Transcriptional regulators are a broad class of proteins that alter gene expression in response to environmental stimuli. Transmembrane transcriptional regulators (TTRs) are a subset of transcriptional regulators in bacteria that can directly regulate gene expression while remaining anchored in the membrane. Whether this constraint impacts the ability of TTRs to bind their DNA targets remains unclear. Vibrio cholerae uses two TTRs, ChiS and TfoS, to activate horizontal gene transfer by natural transformation in response to chitin by inducing the tfoR promoter (PtfoR). While TfoS was previously shown to bind and regulate PtfoR directly, the role of ChiS in PtfoR activation remains unclear. Here, we show that ChiS directly binds PtfoR upstream of TfoS, and that ChiS directly interacts with TfoS. By independently disrupting ChiS-PtfoR and ChiS-TfoS interactions, we show that ChiS-PtfoR interactions play the dominant role in PtfoR activation. Correspondingly, we show that in the absence of ChiS, recruitment of the PtfoR locus to the membrane is sufficient for PtfoR activation when TfoS is expressed at native levels. Finally, we show that the overexpression of TfoS can bypass the need for ChiS for PtfoR activation. All together, these data suggest a model whereby ChiS both (1) recruits the PtfoR DNA locus to the membrane for TfoS and (2) directly interacts with TfoS, thereby recruiting it to the membrane-proximal promoter. This work furthers our understanding of the molecular mechanisms that drive chitin-induced responses in V. cholerae and more broadly highlights how the membrane-embedded localization of TTRs can impact their activity.